Obtaining of Carbon Fibers Based Composite Materials and Study of Their Mechanical Properties (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, theoretical and experimental methods have been developed for obtaining and studying effective thermomechanical characteristics - residual stresses and deformations in panels made of nanomodified materials with an asymmetric reinforcement scheme. The study of the residual stress-strain state of structural elements made of carbon fiber reinforced plastic using the values ​​of thermoelastic characteristics of composite monolayers identified on the basis of the developed methods made it possible to reveal the possibility of reducing the residual stress-strain state in structures with asymmetric reinforcement schemes.